2000
DOI: 10.1073/pnas.070506797
|View full text |Cite
|
Sign up to set email alerts
|

A sequence resembling a peroxisomal targeting sequence directs the interaction between the tetratricopeptide repeats of Ssn6 and the homeodomain of α2

Abstract: The tetratricopeptide repeat (TPR) is a 34-aa sequence motif, typically found in tandem clusters, that occurs in proteins of bacteria, archea, and eukaryotes. TPRs interact with other proteins, although few details on TPR-protein interactions are known. In this paper we show that a portion of a loop in the homeodomain of the DNA-binding protein ␣2 is required for its recognition by the TPRs of the corepressor Ssn6. The amino acid sequence of this loop is similar to the sequences recognized by the TPRs of an en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 41 publications
3
14
0
Order By: Relevance
“…This conclusion is based on (i) the demonstration that the binding of Tup1 to the N terminus of ␣2 is required for Tup1 to block the ubiquitination and turnover of proteins containing the Deg1 signal from ␣2 (Fig. 4 and 5), (ii) the finding that Tup1 and Ssn6 are associated together in a protein complex (39,44), and (iii) the observation, noted above, that Ssn6 binds directly to the homeodomain in the C-terminal domain of ␣2 (34,36). Furthermore, we have observed that the stabilization of the ␣2 protein by TUP1 and SSN6 overexpression is abolished by mutations that impair ␣2-corepressor binding (Fig.…”
Section: Vol 26 2006mentioning
confidence: 99%
See 3 more Smart Citations
“…This conclusion is based on (i) the demonstration that the binding of Tup1 to the N terminus of ␣2 is required for Tup1 to block the ubiquitination and turnover of proteins containing the Deg1 signal from ␣2 (Fig. 4 and 5), (ii) the finding that Tup1 and Ssn6 are associated together in a protein complex (39,44), and (iii) the observation, noted above, that Ssn6 binds directly to the homeodomain in the C-terminal domain of ␣2 (34,36). Furthermore, we have observed that the stabilization of the ␣2 protein by TUP1 and SSN6 overexpression is abolished by mutations that impair ␣2-corepressor binding (Fig.…”
Section: Vol 26 2006mentioning
confidence: 99%
“…6C and D). These experiments utilized a mutant form of ␣2 containing the L10S and R173A amino acid substitutions; these single mutations have been isolated previously and shown to disrupt the ␣2-Tup1 and ␣2-Ssn6 interactions, respectively (22,34). The ␣2 L10S/R173A double mutant was expressed in cells, and the degradation of this protein was examined by pulse-chase assays.…”
Section: Vol 26 2006mentioning
confidence: 99%
See 2 more Smart Citations
“…Pex5p, a 64-69 kDa protein, has TPR (tetratricopeptide repeat) motifs in the Cterminal part and is localized in the cytosol. The TPR motif that consists of 34 amino acids is necessary and sufficient for the binding of Pex5p (Brocard et al, 1994;Smith and Johnson, 2000;Terlecky et al, 1995). On the other hand, PEX5 genes in plants and humans have been cloned based on the sequence of yeast PEX5 gene (Brickner et al, 1998;Kragler et al, 1998;Wiemer et al, 1995;Wimmer et al, 1998).…”
Section: Introductionmentioning
confidence: 99%